PENERAPAN PEMBELAJARAN PROJECT BASED LEARNING (PJBL) MENGGUNAKAN DOMINO KEANEKARAGAMAN HAYATI INDONESIA (DOMINOKHAI) UNTUK MENINGKATKAN KEMAMPUAN COMPUTATIONAL THINKING PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V SD N PENGKOL 01 - Yusehadi, Dahestin; Veronika Unun Pratiwi; Agus Sri Antana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low computational thinking ability of the science subject of biodiversity material in grade V students of SD N Pengkol 01. This study aims to determine the application of the Project Based Learning (PjBL) model in improving the computational thinking ability of science in grade V students of SD N Pengkol 01. This study uses a Classroom Action Research (PTK) design with the Kemmis & Taggart model consisting of 4 stages, namely: (1) Planning stage, (2) Implementation stage, (3) Observation stage, and (4) Reflection stage carried out in two cycles. The subjects used in this study were 25 grade V students of SD N Pengkol 01. The types of data used are quantitative and qualitative data. The results of the study showed an increase in computational thinking ability. The average class value in cycle I reached a percentage completion of 72% and increased in cycle II by 88%. So, it can be concluded that the application of the Project Based Learning learning model can improve the computational thinking skills of class V students of SD N Pengkol 01.